THE MECHANISM BASED ON AN IMPROVED RISK MODEL OF USE RESTRICTION - Kobiljanov Sh. N. (Innovate Conferences, 2026)
This in the article commerce banks information in systems use restriction in the process risks assessment and to manage aimed at improved dynamic risk model offer is being used . use management models main their weaknesses static to the character ownership , risks between dependency enough at the level into account not being able to and extreme situations assessment of opportunity limitedness analysis This is done . problems eliminate to grow risk probability for the purpose and damage level to time related change , inter-risk correlation , optimal allocation of resources , tail risk ( VaR) and CVaR ) analysis and of the system again recovery level into account recipient complex approach working is issued . Offer commercial model banks information in systems use restriction mechanism dynamic in case organization information safety increase and from resources effective use opportunity gives .
Keywords: information security , commerce banks , use limitation , risk model , dynamic risk, VaR , CVaR , extreme risks.